MODELING OF PUBLIC RESULTS OF IMPLEMENTATION OF MEASURES OF STATE REGULATION FOR CONSUMERS AND PRODUCERS OF AGRICULTURAL SECTOR - Іванько, А. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article is focused on the significance of clarifying of the measures of state regulation of economic activity of the subjects of supply of agricultural products; due to the importance of solving of problems of food supply of the population. The effectiveness of using the graphic method and modeling apparatus for economic situations to handle the adoption of managerial decisions is emphasized. The purpose of the article is to justify the procedures for modeling public results from the introduction of regulatory measures for consumers and producers of the agrarian sector. An example of the application of the quota mechanism is the order of modeling of the public effect by determining the total winnings of agricultural producers; the total losses of consumers and the general social result. It is emphasized that the criterion for introducing a quota mechanism is the predominance of producers' preferences over consumer losses. It is possible to introduce quota for solving public problems. It emphasizes the need to determine the sources of funding and the duration of this measure; since the long-term use of economically unreasonable measures undermines the economic foundations of society's life.